Apache Solr enterprise search server : enhance your searches with faceted navigation, result highlighting, relevancy-ranked sorting, and much more with this comprehensive guide to Apache Solr 4 /: enhance your searches with faceted navigation, result highlighting, relevancy-ranked sorting, and much more with this comprehensive guide to Apache Solr 4. (2015) - Smiley, David
No abstract available